An agent-based model for refined cognitive load and reading performance in reading companion robot - Ghanimi, Hayder M. A.; Ab. Aziz, Azizi; Ahmad, Faudziah (Universiti Teknikal Malaysia Melaka, 2017)
This paper presents the importance of modeling dynamical behaviors of human cognitive states that serves as a core foundation in creating intelligent and responsive systems. It discusses in detail the development of a dynamical model of cognitive load and reading performance which acts as the central component of creating a reading companion robot. Simulations results show realistic behaviour patterns that adhere to the literature. Finally, the results produced from an automated verification approach to validate the internal correctness of the proposed model using Temporal Trace Language (TTL) are shown.